A Critical Review on the Unexplored Therapeutic Treasure of Himalayan Ayurvedic Drug Daruharidra (Berberis Aristata) - Ahamad, Javed; Kaskoos, Raad A; Ali, Faraat; Mir, Showkat R. (Current Traditional Medicine, 2021)
Ayurveda captured almost all herbs in its indications for therapeutics from the period of Vedas. More than 700 plants are discussed elaborately in various classics of Ayurveda of different periods. Berberis aristata DC (Berberidaceae), an Indian medicinal plant, is an Ayurvedic herb used since ancient times. It is commonly known as Daruharidra and Daruhaldi. The plant is useful as an antipyretic, antibacterial, antimicrobial, antihepatotoxic, anti-diabetic, anticancer, antioxidant, and hypolipidemic agent. Our main objective was to collect information about the active constituents and major pharmacological actions of B. aristata. The review of the literature included PubMed and Science Direct searches with ‘Berberis aristata’ and ‘Daruharidra’ as initial keywords. This review aims to highlight the ethnomedicinal and pharmacological uses of B. aristata, which will give insights into developing potentially new bioactives from the plant scaffolds. This review also highlights the phytochemicals isolated from different parts of B. aristata. Daruharidra is a rich source of chemically novel compounds, such as berberine, and needs elaborate screening strategies to dwell into the pharmacological effects at the molecular level.
Keywords: Phytochemistry